The apparently less fortunate in the society : revisiting islamic moral law - Khan, Israr Ahmad; Elatrash , Radwan Jamal Yousef (Serial Publication Private Limited India, 2015)
Every human setting comprises both the fortunate and the unfortunate. Most of the societies take special care of the unfortunate—socially downtrodden, economically repressed, physically handicapped, and mentally retarded. Islam does not look at the unfortunate as the wretched and the condemned. It declares that different human phenomena, happy and sad are solely for the purpose of testing the men and women to see who does good deeds and deserves to be rewarded in the life hereafter. Islam makes it binding on its followers to treat the unfortunate justly and generously. For that matter it prescribes general and specific laws. The Qur’an and Prophetic Traditions have both dealt with these provisions. The present article represents humble attempt to highlight and explain Islamic approach towards the less fortunate in the society.